2014
DOI: 10.1007/s00244-014-0073-z
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Behavior Changes in Surubim Acutely Exposed to a Glyphosate-Based Herbicide

Abstract: This study examined the effect of glyphosate-based herbicide (Roundup Original), the major herbicide used in soybean crops in Mato Grosso state, at concentrations of 0, 2.25, 4.5, 7.5, and 15 mg L(-1) on metabolic and behavior parameters of the hybrid fish surubim in an acute exposure lasting 96 h. Glycogen content, glucose, lactate, and protein levels were measured in different tissues. Plasma levels of cholesterol, alanine aminotransferase (ALT), and aspartate aminotransferase (AST) were also determined. Ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 37 publications
3
5
0
Order By: Relevance
“…For the swimming behavior of rainbow trout larvae exposed to single pesticides, we observed that GLY (100 µg/L) induced hyperactivity of larvae, increasing their velocity and mobility under light stimulation [ 28 ]. Similar observations were obtained by [ 24 , 49 , 50 ] in different fish species. On the other hand, larvae exposed to CPF (3 µg/L) were significantly less mobile than non-exposed larvae [ 34 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For the swimming behavior of rainbow trout larvae exposed to single pesticides, we observed that GLY (100 µg/L) induced hyperactivity of larvae, increasing their velocity and mobility under light stimulation [ 28 ]. Similar observations were obtained by [ 24 , 49 , 50 ] in different fish species. On the other hand, larvae exposed to CPF (3 µg/L) were significantly less mobile than non-exposed larvae [ 34 ].…”
Section: Discussionsupporting
confidence: 90%
“…Because of its extensive use, especially in genetically modified crops [ 16 ], high concentrations (ranging from 7.5 to 700 µg/L) have been found in different streams and lakes near agricultural basins [ 17 , 18 , 19 ]. Several reports have highlighted the sub-lethal effects of GLY on fish in particular on DNA integrity [ 20 , 21 , 22 ], acetylcholinesterase (AChE) inhibition [ 23 ], swimming behavior alterations [ 24 , 25 ], and antioxidant enzyme activities [ 26 , 27 ]. We reported that, following a 3-week embryo-larval exposure to glyphosate (0.1 and 1 mg/L), rainbow trout larvae exhibited reduced head size when compared to control larvae.…”
Section: Introductionmentioning
confidence: 99%
“…Srivastava et al (1995) reported increased opercular movements in malachite green exposed Heteropneustes fossilis. As observed during (30 & 60 d) exposure, the decrease in opercular movement has also been noticed in other fishes on exposure to pesticides (Okechukwu et al, 2013;Sinhorin et al, 2014).…”
Section: Opercular Movementssupporting
confidence: 67%
“…Glyphosate [ N ‐(phosphonomethyl)glycine] (GLY) is a broad‐spectrum systemic herbicide with an increasing use in the recent years, particularly in the control of weeds in genetically modified crops (Sinhorin et al ., ,b). The commercial Roundup ® formulation contains GLY as an active ingredient (~41%) along with a non‐ionic surfactant polyethoxethyleneamine (~59%) and other components (Cox, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies examined the ecotoxicity of GBH towards aquatic animals (Albinati et al ., ; Jiraungkoorskul et al ., ; Lushchak et al ., ; Rocha et al ., ; Sinhorin et al ., ,b), indicating fish as a target group for determining GLY or GBH ecotoxicity. The mode of action (MoA) of GBH in fish species has been associated to the production of the reactive oxygen species, to the changes in the antioxidant enzymes activities (e.g.…”
Section: Introductionmentioning
confidence: 99%